1991
DOI: 10.1080/00071669108417396
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term goose breeding for egg production and crammed liver weight

Abstract: 1. Results of an 8-year (1981 to 1988) period of breeding geese for egg production and crammed liver weight, including phenotypic and/or genetic parameters for various traits (1982 to 1985), as well as line tests (1987 to 1988), are summarised for two lines. 2. The regressed annual genetic gains over years were 2.7 eggs and 30.8 g crammed liver. However, there was a decline in the rate of genetic progress after 4 years of selection. 3. Heritability estimates were found to be relatively high for most traits, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…As a result of 13-year selection, Schneider (1987) increased egg production by 8 eggs. Shalev et al (1991) found an annual breeding progress of 2.7 eggs in a flock of geese.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of 13-year selection, Schneider (1987) increased egg production by 8 eggs. Shalev et al (1991) found an annual breeding progress of 2.7 eggs in a flock of geese.…”
Section: Discussionmentioning
confidence: 99%
“…Data for all traits and costs involved were obtained from official bulletins published in Israel (Israel Goose Breeding & Research Farm, 1964to 1995, UK (ADAS, 1981), Canada (Ontario Ministry of Agriculture and Food, 1978), and in USA (Naber, 1979), from reports on the USA-Israel Agriculture & Development (BARD) Fund goose project (Shalev et al, 1982(Shalev et al, -1985, from chapters of Pingel (1990a, b), Shalev et al (1991) and from studies of Shalev (1995). All prices are in US dollars.…”
Section: Methodsmentioning
confidence: 99%
“…Assuming selection would be carried out at least for growth rate and egg production with half the genetic (Shalev et al, , 1991(Shalev et al, , 1995Pingel, 1990a,b;Merritt, 1962). b Based on selection pressure of 20%.…”
Section: Replacement Policymentioning
confidence: 99%
See 1 more Smart Citation
“…With rapid early growth and superior meat production performance, fleshy breeds of geese have high economic benefits; however, poor reproductive performance (low egg production of approximately 30-40 eggs per year) has prevented production on a large scale (Shalev et al, 1991). Laying performance in poultry is closely related to the development of ovarian follicles and the establishment of the follicle hierarchy (Koelkebeck et al, 2001).…”
Section: Introductionmentioning
confidence: 99%